Two-Mode Photon-Number Correlations Created by Measurement-Induced Nonlinearity - Meier, Torsten; Hoepker, Jan Philipp; Protte, Maximilian; Eigner, Christof; Silberhorn, Christine; Sharapova, Polina R.; Sperling, Jan; Bartley, Tim (Conference on Lasers and Electro-Optics: Applications and Technology)
We demonstrate theoretically and experimentally complex correlations in the photon numbers of two-mode quantum states using measurement-induced nonlinearity. For this, we combine the interference of coherent states and single photons with photon sub-traction.

Flexible source of correlated photons based on LNOI rib waveguides - Ebers, Lena; Ferreri, Alessandro; Hammer, Manfred; Albert, Maximilian; Meier, Cedrik; Förstner, Jens; Sharapova, Polina R. (Journal of Physics: Photonics)
Lithium niobate on insulator (LNOI) has a great potential for photonic integrated circuits, providing substantial versatility in design of various integrated components. To properly use these components in the implementation of different quantum protocols, photons with different properties are required. In this paper, we theoretically demonstrate a flexible source of correlated photons built on the LNOI waveguide of a special geometry. This source is based on the parametric down-conversion (PDC) process, in which the signal and idler photons are generated at the telecom wavelength and have different spatial profiles and polarizations, but the same group velocities. Distinguishability in polarizations and spatial profiles facilitates the routing and manipulating individual photons, while the equality of their group velocities leads to the absence of temporal walk-off between photons. We show how the spectral properties of the generated photons and the number of their frequency modes can be controlled depending on the pump characteristics and the waveguide length. Finally, we discuss special regimes, in which narrowband light with strong frequency correlations and polarization-entangled Bell states are generated at the telecom wavelength.
Keywords: tet_topic_waveguide

Multimode integrated SU(1,1) interferometer - Ferreri, A.; Santandrea, Matteo; Stefszky, Michael; Luo, Kai Hong; Herrmann, Harald; Silberhorn, Christine; Sharapova, Polina (Conference on Lasers and Electro-Optics)
We present a frequency multimode integrated SU (1,1) interferometer with a polarization converter and strong signal-idler photon correlations. Phase sensitivity below the shot noise limit is demonstrated, various filtering and seeding strategies are discussed.

Spectrally multimode integrated SU(1,1) interferometer - Ferreri, Alessandro; Santandrea, Matteo; Stefszky, Michael; Luo, Kai Hong; Herrmann, Harald; Silberhorn, Christine; Sharapova, Polina R. (Quantum)
Nonlinear SU(1,1) interferometers are fruitful and promising tools for spectral engineering and precise measurements with phase sensitivity below the classical bound. Such interferometers have been successfully realized in bulk and fiber-based configurations. However, rapidly developing integrated technologies provide higher efficiencies, smaller footprints, and pave the way to quantum-enhanced on-chip interferometry. In this work, we theoretically realised an integrated architecture of the multimode SU(1,1) interferometer which can be applied to various integrated platforms. The presented interferometer includes a polarization converter between two photon sources and utilizes a continuous-wave (CW) pump. Based on the potassium titanyl phosphate (KTP) platform, we show that this configuration results in almost perfect destructive interference at the output and supersensitivity regions below the classical limit. In addition, we discuss the fundamental difference between single-mode and highly multimode SU(1,1) interferometers in the properties of phase sensitivity and its limits. Finally, we explore how to improve the phase sensitivity by filtering the output radiation and using different seeding states in different modes with various detection strategies.

Managing spectral properties and Schmidt mode content of squeezed vacuum light using sum-frequency converter - Sukharnikov, Vladislav; Sharapova, Polina; Tikhonova, Olga (Optics & Laser Technology)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials